Business Model Analysis from the Activity System Perspective: A Design Science Research - Marina Gaspareto (BAR - Brazilian Administration Review, 2020)
Understanding a business model is at the core of organizational strategy, competitiveness, and business sustainability. Descriptive approaches to understand business models are often based on the analysis of their components by looking at organizational assets, resources, plans, and competencies. Although there are numerous contributions in the literature, few guidelines are offered regarding an Activity System perspective, in a prescriptive rather than a descriptive way. In this study, we propose a pragmatic solution to help cover this literature gap and to extend on previous studies. A Design Science Research approach was adopted including a multicase study of four business companies we examined in order to create a method for business model analysis from an Activity System perspective. The resulting artefact of the study is illustrated with data from the empirical cases. Three analytical movements are described as well as prescribed: dimensions analysis (i.e., business definition, customer segment, value proposition, profit logic, critical factors of value proposition, and Activity System); visual representation including illustrations of its Activity System; and competitive analysis including prospection for changes and innovations. Finally, the artefact is discussed in relation to its quality, utility, and usability.